2019
DOI: 10.18502/ehj.v5i1.1201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lower Limb Resistance Exercise with Elastic Band on Balance, Walking Speed, and Muscle Strength in Elderly Women

Abstract: Introduction: The aim of this study was to investigate the effect of an 8-week resistance exercise program on balance, walking speed, and muscle strength in elderly women.   Methods: This randomized controlled trial was performed on 50 elderly women aged 60-66 years who were assigned to two groups of experimental and control. The Time Up and Go test, was used to measure dynamic balance, Romberg's test was used to measure static balance, and the 10 Meter Walk Test was used to measure walking speed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Prosedur latihan sebagai berikut (Vafaeenasab et al, 2019): 1) Warm up selama 5 menit. Latihan terdiri dari forward leg swing, lateral leg swing, hip circle, knee circle, high knee, stepping sideway, stepping forward, stepping backward dengan bertepuk tangan.…”
Section: Gambar 1 Metode Penyampaian Materi Latihan Aktivitas Fisik M...unclassified
See 1 more Smart Citation
“…Prosedur latihan sebagai berikut (Vafaeenasab et al, 2019): 1) Warm up selama 5 menit. Latihan terdiri dari forward leg swing, lateral leg swing, hip circle, knee circle, high knee, stepping sideway, stepping forward, stepping backward dengan bertepuk tangan.…”
Section: Gambar 1 Metode Penyampaian Materi Latihan Aktivitas Fisik M...unclassified
“…Peserta memahami dan melakukan latihan di rumah masing-masing secara mandiri. Latihan fisik secara rutin mampu meningkatkan kekuatan otot dan kemampuan fungsional (Vafaeenasab et al, 2019). Kemampuan untuk berjalan dengan jarak yang lebih baik dinilai berasosiasi langsung terhadap ketahanan fisik dan mobilitas (Pellicer et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Elastic bands are generally made from thin pieces of plastic and are available in a variety of specifications for different training needs. With elastic bands, resistance may be increased or decreased based on the user's muscle strength (Vafaeenasab et al, 2019). Studies have shown elastic band exercises to be low-impact and high-stability activities that improve cardiopulmonary and musculoskeletal function, muscle endurance, flexibility, lower body balance, and quality of life in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of resistance training include building skeletal muscle mass; enhancing muscle strength, flexibility, and dynamic balance; improving walking speed; and reducing age-related losses in muscle strength, muscle mass, and bone density. Resistance training concurrently improves physical functions, including sit-to-stand time, walking endurance and speed, balance, and fall avoidance, which improve quality of life and prolong independent living (Kuo et al, 2016; Mora & Valencia, 2018; Vafaeenasab et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation